Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Inap Pada Rumah Sakit Syafira Pekanbaru - Jeli Nata Liyas (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
This research was conducted at Syafira Hospital Pekanbaru. The purpose of this study was to determine the effect of Service Quality on Patient Satisfaction at Syafira Hospital Pekanbaru. The population in this study was 6,590 patients. The technique used in this study is non-probability sampling with the Accidental Sampling approach with a total of 99 patients as respondents. In this study, data was collected through questionnaires to 99 patients at Syafira Hospital Pekanbaru. The quantitative analysis used in this research is to use validity test, reliability test, normality test, simple linear regression, t test and the coefficient of determination test. Judging from the results of the calculation of simple linear regression test obtained Y = 16,422 + 0.492 X and the t test shows that t count> t table (8,254> 1,984) this means that service quality has a significant effect on inpatient satisfaction at Syafira Hospital Pekanbaru. The magnitude of the influence of Service Quality on Inpatient Satisfaction is 41.3% while the remaining 58.7% is influenced by other variables